2011
DOI: 10.1080/02522667.2011.10700114
|View full text |Cite
|
Sign up to set email alerts
|

A typology and assessment of human resources performance in the financial services industry: The human resources scorecard perspective

Abstract: Under the trend of fl ourishing development and rapid transformation in global fi nancial markets, the domestic fi nancial service industry needs to adjust their strategies more actively to accommodate to such a global trend. As these changes can not be implemented without manpower, the importance of human resources is more signifi cant then ever. The human resource management performance plays a vital role in reinforcing a company's competitive advantage. The way to measure human resource performance is an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Menurut (Panudju et. al., 2017, Chuang et. al., 2011 HRSc dapat mengukur efektivitas maupun efisiensi SDM sehingga dapat menggambarkan kontribusi SDM tersebut bagi kesuksesan suatu organisasi.…”
Section: Hasil Penelitian Dan Pembahasan Pengertian Human Resource Sc...unclassified
“…Menurut (Panudju et. al., 2017, Chuang et. al., 2011 HRSc dapat mengukur efektivitas maupun efisiensi SDM sehingga dapat menggambarkan kontribusi SDM tersebut bagi kesuksesan suatu organisasi.…”
Section: Hasil Penelitian Dan Pembahasan Pengertian Human Resource Sc...unclassified
“…Jääskeläinen and Laihonen (2013) stressed the need to understand the challenges associated with non-traditional PM and the importance of understanding the process of applying them in a service environment. Service output hinges on individual employees possessing adequate skill and experience, the quality of the production system and the value of interactions between employees and customers (Chuang et al , 2011; Masum et al , 2015; Grönroos and Ojasalo, 2004; Lonnqvist and Sillanpää, 2011; Jääskeläinen and Laihonen, 2013).…”
Section: Relevant Literaturementioning
confidence: 99%
“…For instance, Harris and Mongiello (2001) highlighted that managers initially give more emphasis to learning and growth when they seek to improve hotel’s business performance. However, Chuang et al (2011) have found that the customers aspect is the most important when measuring performance in the financial service industry, whereas Wang (2012) found that internal processes – knowledge management – is the most important aspect in consulting firms and that learning and growth was ranked second. Jääskeläinen and Laihonen (2013) believe that the customer aspect has not been fully recognized when measuring the performance of service firms, even though service firm’s performance is a customer-specific phenomenon.…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A low sense of personal accomplishment is a decrease in the sense of achievement as a result of the individual's negative feelings towards work (Chuang et al 2011). These three dimensions come together in a certain process and cause individuals to display symptoms of burnout syndrome.…”
Section: Introductionmentioning
confidence: 99%